1989
DOI: 10.1111/j.1476-5381.1989.tb11780.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the GABAB agonist, (−)‐baclofen, on neurones in deep dorsal horn of the rat spinal cord in vitro

Abstract: 1 The electrophysiological actions of the GABAB agonist, (-)-baclofen, on deep dorsal horn neurones were studied using an in vitro preparation of the spinal cord of 9-16 day old rat.2 On all neurones tested, (-)-baclofen (100nM-30.uM) had a hyperpolarizing action which was associated with a reduction in apparent membrane input resistance. The increase in membrane conductance was dose-dependent and had a Hill coefficient of 1.0.3 The (-)-baclofen-activated hyperpolarization persisted in the presence of bicucull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 25 publications
6
24
0
Order By: Relevance
“…The present experiments did not reveal a peptide-mediated EPSP, EPSPs were consistently and completely blocked by CNQX, and a prolonged EPSP was never observed, even after high-frequency presynaptic stimulation. Our finding that baclofen had no postsynaptic effect on spinal cord neurons is consistent with some, but not all previous reports (Lev-Tov et al, 1988;Peng and Frank, 1989; but see also Allerton et al, 1989;Kangrga et al, 199 1). Differences between the present findings and these previous reports may be due to our use of a dissociated cell preparation, or may reflect the use of embryonic tjssue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present experiments did not reveal a peptide-mediated EPSP, EPSPs were consistently and completely blocked by CNQX, and a prolonged EPSP was never observed, even after high-frequency presynaptic stimulation. Our finding that baclofen had no postsynaptic effect on spinal cord neurons is consistent with some, but not all previous reports (Lev-Tov et al, 1988;Peng and Frank, 1989; but see also Allerton et al, 1989;Kangrga et al, 199 1). Differences between the present findings and these previous reports may be due to our use of a dissociated cell preparation, or may reflect the use of embryonic tjssue.…”
Section: Discussionsupporting
confidence: 93%
“…GABA, receptors on neurons in the spinal cord (Allerton et al, 1989;Wang and Dun, 1990;Kangrga et al, 1991) and brain (Newberry and Nicoll, 1984;Gahwiler and Brown, 1985;Howe et al, 1987;Connors et al, 1988) are coupled to the activation of a potassium conductance. Interestingly, GABAergic inputs onto hippocampal CA1 pyramidal neurons are presynaptically inhibited via this potassium conductance .…”
Section: Mechanisms Of Presynaptic Inhibitionmentioning
confidence: 99%
“…Second, baclofen also had a prominent postsynaptic effect. As described previously in the hippocampus (Newberry & Nicoll, 1984) and rat dorsal horn (Allerton et al 1989), the hyperpolarization induced by baclofen in plateau neurones in the turtle was associated with decreased input resistance. In hippocampal pyramidal neurones, the baclofen-induced hyperpolarization is produced by a K¤ conductance (Newberry & Nicoll, 1984) which is blocked by low concentrations of Ba¥ (G ahwiler & Brown, 1985).…”
Section: Metabotropic Inhibitionsupporting
confidence: 76%
“…In the hippocampus (G ahwiler & Brown, 1985) and spinal cord (Allerton, Boden & Hill, 1989) the hyperpolarization mediated by GABAB receptors is sensitive to low concentrations of Ba¥. In agreement, extracellular Ba¥ (1-2 mÒ, n = 7) decreased the baclofen-induced hyperpolarization (not illustrated) and shunt (Fig.…”
Section: Inhibitory Mechanisms Mediated By Gabab Receptor Activationsupporting
confidence: 69%
“…It has already been demonstrated that baclofen selectively inhibits the release of excitatory amino acids like aspartate and glutamate (Johnston et al, 1980;Davies, 1981;Lanthorn & Cotman, 1981). In fact, the activation of GABAB receptors, which are also located on nerve terminals, leads to the inhibition of neurotransmitter release via the opening of K+ channels and consequent neuronal hyperpolarization (Bowery et al, 1980;Newberry & Nicoll, 1984;1985;Raiteri et al, 1989;Potier & Dutar, 1993) or inhibition of calcium currents (Zhu & Chuang, 1987;Allerton et al, 1989;Maguire et al, 1989). Furthermore, the neuronal inhibitory effects of low doses of systemically administered baclofen, which correspond to the dose-range used in this study, on the synaptic excitatory transmission in the CNS, is mediated by a presynaptic action (Pierau & Zimmerman, 1973;Fox et al, 1978;Davies, 1981).…”
Section: Discussionmentioning
confidence: 99%